Evolution of the World Bank’s Thinking on Governance - Lateef, K. Sarwar (World Bank, Washington, DC, 2017)
The preparation work for the 2017 World Development Report on Governance and the Law in 2016 will coincide with the 25th anniversary of the World Bank’s decision to broaden its ongoing work on public sector management to embrace key issues of governance in the Bank’s borrowing countries. This paper provides a broad overview of the major Bank reports on governance that went through a review process at a sufficiently high level in the institution that they can reasonably be described as reflecting the Bank’s considered views at the time on the subject. The objective is to review the evolution of the Bank’s thinking on governance and assess the relevance and effectiveness of the work and its implications for the forthcoming World Development Report. Section two of this paper begins with a brief account of how the Bank came to focus on issues of governance, reviewing the major upheaval of governance in many of the Bank’s borrowing countries in the 1980s, the legal constraints the Articles of Agreement impose on the Bank’s work on governance, and a brief overview of the Bank’s initial policy statement on governance issued to the Bank’s Board in June 1991. Section three reviews major Bank work on governance as reflected in successive World Development Reports and examines the Bank’s analysis of the issue of corruption, reviewing how the Bank’s thinking on this symptom of poor governance has evolved. Section four steps back to assess what the Bank got right and some of the issues it missed or failed to address adequately. Section five draws attention to the dramatic changes experienced by the developing world in these past 25 years, and points to the need to better understand the implications of these changes for the governance context facing developing countries.